Book Review: History of Vocational Education and Training in Europe - Tyson, Ruhi (International Journal for Research in Vocational Education and Training, 2018)
The book is volume 14 in the series Studies in Vocational and Continuing Education. Series editors are Philipp Gonon & Anja Heikkinen. Volume 14, History of Vocational Education and Training in Europe: Cases, Concepts and Challenges is edited by Esther Berner, Professor for Educational Science, Helmut-Schmidt University in Hamburg, Germany, and Philipp Gonon, Professor for VET and Teacher Training, University of Zurich, Switzerland.